House of secrets - Battle of the beasts - Columbus, Chris 1958-; Vizzini, Ned 1981-2013 (Balzer + Bray / HarperCollins, 2014)
The Walker children's struggle to fit in at a new school is complicated by the return of Dahlia Kristoff, who casts Brendan, Eleanor, and Cordelia back into book worlds, from which escape will be more difficult than before
Keywords: Frères et soeurs / Romans; Habitations / Romans; Sorcières / Romans; Voyages dans le temps / Romans; Merveilleux / Romans; Magie / Romans; Livres / Romans